Coping and its relationship with quality of life in patients with type 2 diabetes mellitus (European Journal of Health Research, 2018)
Diabetes mellitus is among the main health problems in Mexico generating challenges to the health system (insufficient staff, little infrastructure, lack of medicines) due to the growing number of cases diagnosed and the increase in deaths. In Mexico, for 2015, 11.463.000 diabetic people were reported, this caused that our country occupies the sixth place in the world in prevalence of this disease (I.F.D, 2015).The objective was to know if coping is related to quality of life in patients with Diabetes Mellitus type 2. It was a correlational study; the type of sampling was non-probabilistic of intentional type, in a sample of 230 adults. We used the Stress Coping Questionnaire (CAE, by Sandín & Chorot, 2003) and the DQOL, "Quality of life in diabetes" (Robles, 2003). An invitation was made to the patients through an informed consent letter when they went to the health clinic. The results show that the knowledge, control and treatment that the patients have about the disease is deficient and in addition, there were significant moderate positive correlations between the various factors that integrate each variable studied here, thus, the adjustment and adaptation towards the disease represent important challenges of bio-psycho-social intervention.
Keywords: Coping; quality of life; Diabetes Mellitus